Pedagogical Review of Edulogy LMS: Case Study on Indonesian Educational System - Rizki Zakwandi; Jumadi Jumadi; Habibah Khusna Baihaqi; Ade Yeti Nuryantini (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Learning Management System (LMS) was an alternative learning where teachers and students interacted systematically. Besides, LMS also described the digitalization solutions of the education system. This study aimed to analyze the pedagogical aspects of LMS Edulogy. The research meth-od used was a case study on two LMS Edulogy dashboards, namely the dashboard of the vice principal of curriculum and the dashboard of the teacher. In addition, user responses were also collected by distributing questionnaires to 144 teachers and 8 vice-principals of the curriculum. The results showed that the LMS Edulogy was quite good at facilitating the vice principal of the curriculum and teachers in carrying out their duties. As many as 64.44 percent of the duties of the vice principal of curriculum and 60 percent of the duties of the teachers have been facilitated in LMS Edulogy. Overall, the level of satisfaction at LMS Edulogy classified as good where 75 percent of the vice principal in the curriculum field are satisfied and 67.64 percent of the teachers were expressed satisfaction. The results of this study were expected to be a reference for the next development related to LMS and become a consideration for using LMS Edulogy.